Overview of microbes based fabricated biogenic nanoparticles for water and wastewater treatment. - Ali, Imran; Peng, Changsheng; Khan, Zahid M.; Naz, Iffat; Sultan, Muhammad; Ali, Mohsin; Abbasi, Irfan A.; Islam, Tariqul; Ye, Tong (Journal of Environmental Management, 2019)
Abstract Treatment of toxic and emerging pollutants (T&EPs) is increasing the threats to the survival of conventional wastewater treatment (WWTs) technologies. The high installation and operational costs of advanced treatment technologies have shifted the research interest to the development of economical and reliable technology for management of T&EPs. Thus, recently biogenic nanoparticles (BNPs) fabricated using microbes/microorganisms are getting tremendous research interest due to their unique properties (i.e. high specific surface area, desired morphology, catalytic reactivity) for the biodegradation and biosorption of T&EPs. In addition, BNPs can be manufactured using metal contaminated water which indicates a hidden potential for resource recovery and utilization. Therefore, the present study discusses the adsorptive and catalytic performance of BNPs in the removal of T&EPs from water (W) and wastewater (WW). In addition, inspired by the superior performance of BNPs in advance WWT, a model of BNPs based WWT resource recovery and utilization process is also proposed. Finally, main issues i.e. mass production, leaching, poisoning/toxicity, regeneration, reusability and fabrication costs and process optimization are discussed which are main hinders in the transfer of BNPs based WWT technologies from laboratory to commercial scale. Graphical abstract Image Highlights • Fabrication and applications of biogenic nanoparticles (BNPs) in WWT are discussed. • Adsorptive and catalytic performance of biogenic nanoparticles is critically reviewed. • Pollutants removal mechanism via BNPs is explored and compared. • Functioning of BNPs based WWT technology is discussed for commercial applications.